Review on Soluplus®: Pharmaceuticals Revolutionizing Drug Delivery and Formulation Strategies - Mali, Kamalesh Dilip; Shinde, Durgesh Tulshiram; Patil, Kalpesh Ravindra (International Journal of Pharmaceutical Investigation, 2025)
Solubility enhancers are one way to get around the difficulties with medication absorption and dissolution in oral drug delivery, since many novel active pharmaceutical components are not well soluble in water. The efficacy of a novel solubility-enhancing excipient (Soluplus) to enhance intestinal medication absorption. Improved drug release from poorly soluble pharmaceuticals can be achieved via polymer-based solid dispersions, such as Amorphous Solid Dispersions (ASD). Drug release and the rate of precipitation are directly influenced by the polymer concentration in dissolving fluid as well as the polymer and drug release occurring simultaneously. Investigating the polymer’s release in addition to the drug’s release is crucial, in addition to emphasizing the simultaneous measurement of both polymer and drug in the dissolution media, the goal of this critical systematic review was to provide an overview of the existing quantification techniques for commonly used water-soluble polymers, such as Soluplus®.
Keywords: Amorphous solid dispersions; Graft copolymer; Oral drug delivery soluplus; Polymer-based drug release; Solubility enhancers; Soluplus